Marketing Digital And Social Media Improve Content Quality And Implicate The Performance Of Ayobandung.Com - Zulfikar, Taufik; Yudha, Firman Mighty; Kosasih, Kosasih (UNIVERSITAS PAKUAN, 2022)
In the current digital era, the performance of an application can determine the success of a company in competition. The better the performance of an application it will create a competitive advantage or stronger competitiveness. Companies that dominate the market will be guaranteed their survival. Ayobandung.com is a news channel website that uses social media and digital marketing through quality content to improve performance. The purpose of this study is to examine the influence of social media and digital marketing on content quality which has implications for performance. Quantitative methods are used in this study using path analysis as an analytical tool. A sample of 100 people who are viewers. The results of the study show that digital marketing and social media have an influence on content quality both partially and together, digital marketing and content quality have an influence on performance, while social media has no effect on performance.